Measurement of δ18O values in arsenic and selenium oxyanions. (12th December 2012) - Larese‐Casanova, Philip; Blake, Ruth E.
<x xml:space="preserve">Abstract</x> RATIONALE Past stable isotopic studies of selenium and arsenic oxyanions within a biogeochemistry context have focused solely on selenium isotopes due to monoisotopic nature of arsenic and lack of attention to oxygen. A modern quantification method of δ18O values in selenate, selenite, arsenate, and arsenite is presented here, similar to methods for other inorganic oxyanions such as phosphate. METHODS Dissolved oxyanions were recovered after precipitation with silver or barium cations within controlled pH ranges and purified by drying and roasting under vacuum. Oxygen isotope ratio measurements were performed on 250–450 micrograms of solids using continuous flow high‐temperature conversion elemental analyzer/isotope ratio mass spectrometry (CF‐TCEA/IRMS). Each Se and As solid was evaluated for reproducibility and stability of δ18O values and the usefulness of this method for evaluating aqueous phase Se and As oxyanion reactions was addressed. RESULTS Only silver arsenate and barium selenate were shown to have stable, reproducible δ18O values over 5 months and were calibrated to the VSMOW scale. The method was applied to confirm complete exchange of oxygen isotopes between arsenate and solvent water at pH 7 which produced an O‐isotope fractionation between arsenate and water of 6.0‰. Furthermore, the method revealed the ability of oxygen in selenate to kinetically fractionate during reduction to elemental selenium by a green rust compound which produced a fractionation (20.9‰) larger than reported δ80/76Se values for similar reactions. CONCLUSIONS The experimental and analytical conditions for δ18O analysis of Se and As oxyanions were detailed. δ18O analyses of As and Se oxyanions may be useful in biogeochemical studies for tracing chemical reaction pathways, determining environmental sources of Se, or diagnosing specific reaction mechanisms for As and Se oxyanions. Copyright © 2012 John Wiley & Sons, Ltd.